Remote Temperature Monitoring and Control System Using SCADA for Large Industrial Environment - B., Vivekanandam (Journal of Electrical Engineering and Automation, 2024)
In large-scale food companies to ensure product quality and protection, precise temperature control must be maintained. This research presents the design and implementation of a SCADA (Supervisory Control and Data Acquisition) system integrated with a PID (Proportional-Integral-Derivative) control strategy for effective temperature regulation. The system offers operators a comprehensive Human-Machine Interface (HMI) for real-time visualization and control, processes temperature data through a PID controller to maintain a setpoint of 85°C, and continually monitors temperature data in real-time. The simulation results demonstrate that despite outside disruptions, the system can maintain the required temperature within close tolerances, assuring ideal process conditions. Large-scale industrial applications of SCADA systems are emphasized by their function in advanced data analysis, supervisory control, alarm management, and data collecting.
Keywords: HMI; RTU’s; PLC; SCADA System; PID control; Industrial Applications